A Quality Management Concept for Educational Facilities and Infrastructure was Developed in the Industrial Revolution 5.0 - Syafaruddin, Baso (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This paper explores the potential and problems that modern educational institutions have when it comes to managing the quality of their infrastructure and amenities. Every organization, especially educational institutions, must keep up with technological advancements. Therefore, educational institutions must use these difficulties as possibilities to continue to exist as the institutions that will direct and build a civilization in the future. By managing educational infrastructure and amenities in a way that can keep up with the present 5.0-period development, this study attempts to gauge the essence of educational institutions. The study used library methods to get information from reliable sources. To ensure that educational institutions continue to exist, infrastructure and facilities must be updated for the modern 5.0 period. In essence, it has evolved into a requirement that may support the continuation of educational activities.